Karakteristik Pasien Terkonfirmasi Coronavirus disease (COVID-19) di RS X Samarinda Periode Maret-Desember 2020: The Characteristics of Confirmed Patients Coronavirus disease (COVID-19) at RS X Samarinda in March-December 2020 - Ridha Siti Ruhama; Febrina Mahmudah; Yurika Sastyarina (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Coronavirus disease (COVID-19) is a virus that has become a world pandemic including Indonesia. East Kalimantan is a province with a total of 71,092 confirmed cases of covid-19 as of March 28, 2020. The RS X Samarinda has 660 confirmed cases covid-19 during march - December period in 2020. This research aims to identify characteristics of patients covid-19 at RS X Samarinda in March - December 2020. This research is descriptive by retrospective methods. Data collection is conducted quantitatively with a sampling technique. Research instruments are 100 data inclusions of patient medical records. The results of this research show that the dominant 51% are male and 49% are female. The most age groups 34% in the early aged (46-55 years old), with further treatments >7 days as much as 65%. Patients who have 31% komorbides and without comorbidity as much as 69% in the category 87.09% diabetes mellitus. Patients data of 58,82% experienced one of the clinical symptoms of coughing/sniffles/throat pain.